The effects of escape panels on commercial catches of juvenile hakes (Merluccius spp.) off South Africa - Popose, Gcobani (Department of Biological Sciences, 2024)
The South African hake fishery has experienced a decline in catches in recent times and juvenile catches now constitute a large portion of the catches. This study was undertaken to test three different juvenile exclusion panels (square mesh, plastic grid and large mesh) in minimizing the volumes of juvenile hake (primarily Merluccius paradoxus) caught in otter trawl nets. Five trawling vessels were used for this experiment and their catches were compared to those immediately prior to the experiment, and to catches of nine trawling vessels (control vessels) fishing in the same general location during the same period. The control of the deployment of these trawling vessels was a limiting factor in the study, and that influenced the results of this experiment. The results of comparing the proportions of small hake caught by each vessel before and during the experiment indicated that two of the five vessels caught fewer small hake during the experiment. However, this was probably caused by reduced availability of small hake during the experiment. When the different gear types were compared with the controls using a normal approximation of a chi-square test, there were no significant differences in the proportions of small hake caught (square mesh, p = 0.4344; large mesh, proportion increased and plastic grid, p = 0.5617). When a general linear model was applied to the catches and other explanatory variables, no significant differences in the catches of small hake could be attributed to gear type. More investigations of gear selectivity in otter trawl nets are needed, using a more comprehensive data set, and a better-controlled deployment of fishing.